“Waiting time of patients who present at Emergency department of Saint Rita’s hospital, Limpopo Province, South Africa.” - Cimona-Malua, T. C. (University of Limpopo (Medunsa Campus), 2010)
Title: Waiting time of patients who present at Saint Rita’s hospital Emergency Department (ED), Limpopo province, South Africa. Objective: To determine the waiting time for stable patients who present at Saint Rita’s hospital ED, to determine where the longest time is spent by patients in ED and to identify the area of inefficient patients flow. Methods: A descriptive cross-sectional study was conducted in the ED of Saint Rita’s Regional hospital in the province of Limpopo, South Africa. During a one week period, Monday to Friday in July 2010, a daily random sample of 30 patients was monitored. The time In and Out of each step in the process of care was recorded. Waiting time was defined as the time from arrival of the patient in the ED until the start of the consultation by the Medical Officer. Time elapsed was calculated for various steps in care. Demographic data, diagnosis and acuity based on the SATS were obtained from patient’s record. Data capturing was done in window excel and data analysis done using the statistical software SPSS 17. Results: The mean waiting time for stable patients was 252.3 minutes. The mean EDLOS was 360 minutes for stable patients. Result show that 80% of patient attending Saint Rita’s ED are non-urgent (SATS: Green) cases. There was fluctuation of waiting times from Monday to Friday; with Monday having the longest waiting time and Tuesday the shortest waiting time. The waiting time for unstable patients (SATS: Red or Orange) is Zero minute. Patients spent the longest time waiting for registration (60 minutes) and for triage (57 min waiting for vitals and 28 minutes waiting for history taking). Interestingly the extremity of age: the youngest and oldest had lowest waiting time in ED. Areas of inefficient patient flow were registration and triage. Conclusion: This study has determined the waiting time for stable patients attending Saint Rita’s Regional Hospital ED. It has shown that waiting time in ED fluctuates with the day of the week. It has also shown that waiting time in ED varies with age of the patient and volume of patients in ED. Registration and triage have been identified as areas of inefficiency patients flow and recommendations for improvement have been formulated. Sustainability of the performance requires regular follow up from the hospital management.
Thesis (M. Med. (Family Medicine)) -- University of Limpopo (Medunsa Campus), 2010.
Keywords: Emergency medical services